Methyltransferase-Like 3-Mediated m6A Methylation of Hsa_circ_0058493 Accelerates Hepatocellular Carcinoma Progression by Binding to YTH Domain-Containing Protein 1 - Wu, Anqi; Hu, Yuhao; Xu, Yao; Xu, Jing; Wang, Xinyue; Cai, Aiting; Liu, Ruoyu; Chen, Lin; Wang, Feng (Frontiers in Cell and Developmental Biology, 2021)
Circular RNAs (circRNAs) are highly correlated with the progression and prognosis of hepatocellular carcinoma (HCC). In addition, mounting evidence has revealed that N6-methyladenosine (m6A) methylation, a common RNA modification, is involved in the progression of malignancies. In this research, a novel circRNA, hsa_circ_0058493, was proven to be upregulated in HCC, which was correlated with the prognosis of HCC patients. Experimentally, hsa_circ_0058493 knockdown suppressed the growth and metastasis of HCC cells in vivo and in vitro. On the contrary, the overexpression of hsa_circ_0058493 in HCC cells had the opposite effect in vitro. Mechanistic experiments revealed that hsa_circ_0058493 contained m6A methylation sites and that methyltransferase-like 3 (METTL3) mediated the degree of methylation modification of hsa_circ_0058493. Furthermore, YTH domain-containing protein 1 (YTHDC1) could bind to hsa_circ_0058493 and promote its intracellular localization from the nucleus to the cytoplasm. In addition, both si-METTL3 and si-YTHDC1 suppressed HCC cell growth and metastasis, whereas rescue experiments confirmed that overexpression of hsa_circ_0058493 inverted the inhibitory effects of si-METTL3 and si-YTHDC1 on HCC cells. Taken together, this study explored the oncogenic role of m6A-modified hsa_circ_0058493 and found to accelerate HCC progression via the METTL3-hsa_circ_0058493-YTHDC1 axis, indicating a potential therapeutic target for this deadly disease.